Development of microstructure and hydration processes of concrete composites for structures with high durability - Sumariuk, О.V.; Sobko, Y.T.; Chernenko , K.V. (Ways to Improve Construction Efficiency, 2022)
The main processes necessary for the development of microstructure and hydration of concrete and their composites for use in structures with high durability, frost resistance, water resistance are analyzed. The potential development that will ensure the strength of concrete and their composites, which have been modified by a complex of fine additives in the time range up to 365 days, has been determined. The experimental formulation of the concrete mixture, which was modified by a complex of fine modifiers based on microsilica (MK) and metakaolin (MTK), was used for testing. Concrete mixing technology has also been improved. The structure of ultra-high-strength concrete is formed during physicochemical reactions, which are accompanied by the binding of free water with clinker minerals, the formation of a saturated solution of crystal hydrates and their subsequent crystallization. Determining compounds of cement structure are such hydration products as: calcium silicate hydrate with various modifications, portland, calcite. For a more complete picture of the formation of hydration phases in high-strength concrete composites and the effect of ultrafine modifiers, the microstructure of fracture surfaces and their phase composition on the 28-day aging of concrete composites were studied by scanning electron microscopy and energy-dispersive X-wave spectroscopy. Comparative microanalysis and elemental analysis of various concrete composites of high structural strength and density using the methods of X-ray diffraction and energy-dispersive X-wave spectroscopy. However, the presence of Al in the later stages of hydration can also lead to the formation of secondary phases. The molar ratio of CaO to SiO2 in C-S-H is one of the main parameters for determining and controlling the properties of the calcium hydrosilicate system, which can be used to characterize some parameters of concrete durability. The structure of concrete is actually the main factor that determines its mechanical properties and their security throughout the life of the structure. Regularities of formation of structure and properties are common to all types of concrete.